PENGARUH RELIGIUSITAS ISLAMI TERHADAP PEMAAFAN PADA REMAJA Studi Kasus Di Madrasah Aliyah Negeri III Yogyakarta - Ru'iya, Sutipyo (Universitas Ahmad Dahlan, 2013)
Background: This study was developed based on the recent phenomenon of late adolescents are increasingly experiencing problems in their social life, such as brawls, gang, and the anxiety that causes them to crash while in school. This phenomenon indicates the level of forgiveness the less. One factor achieving forgiveness is religiosity. Therefore, this study aimed to determine the relationship of religiosity and forgiveness among adolescents especially students of Madrasah Aliyah III Yogyakarta. Objective: Selection of research subjects in adolescent students of Madrasah Aliyah III Yogyakarta is because Madrasah Aliyah III Yogyakarta Yogyakarta is the MAN model, but it had the same problems of students with students in another schools. Methods: This study use a quantitative approach to the subject of the research is a class XI choses by cluster random sampling from some existing classes. Measurement of psychological symptoms using a scale of forgiveness The Heartland Forgiveness Scale (HFS) and religiosity measured by Moslem Religiosity Personality Inventory (MRPI). Both the scale of the researcher adapted from the original source. The number of respondents in this study were 105 students of class XI IPS-1, IPS-2, IPS-3, IPA-1, and IPA-2. Results: Based on the results of data analysis, it is concluded: that there is a positive relationship between the level of Islamic religiosity and forgiveness among adolescents. The higher the level of Islamic religiosity teenagers will be higher and the lower pemaafannya Islamic religiosity teens will be teens forgiveness anyway. The contribution of Islamic religiosity on forgiveness is at 6.1% . Conclusion: From these results, it can be concluded that to improve forgiveness in adolescents, it needs to be improved its Islamic religiosity.